Identification of peptide adsorbates for strong nanoparticle–nanoparticle binding by lattice protein simulations. (January 2015) - Packwood, Daniel M.; Akagi, Kazuto; Umetsu, Mitsuo
Graphical abstract: Abstract: Nanoparticles with short peptides adsorbed to their surfaces often assemble into interesting structures when suspended solution. In this paper, the interaction between a peptide adsorbed to a surface and another peptide adsorbed to an opposing surface is studied using the lattice protein model. It is found that the interaction strength between the two peptides generally increases as the hydrophobicity of peptides increases. Moreover, there is a preference for hydrophobic amino acids to be neighboring hydrophilic amino acids in cases which yield strong peptide–peptide interactions. These results provide insights for tailoring the strength of nanoparticle–nanoparticle binding by engineering of peptide adsorbates.